Quality and Productivity – Quality & Lean Six Sigma KPIs: Creating a Quality Strategy: Ritz-Carlton Hotel - Mansoor, Najwa (European Journal of Business and Strategic Management, 2025)
Purpose: This study investigates the implementation of Lean Six Sigma methods in Ritz-Carlton Hotel sites in the UAE, with the goal of improving customer satisfaction and operational efficiencies. The DMAIC (Define, Measure, Analyze, enhance, Control) approach is used in this study to completely examine and enhance service quality and efficiency using data-driven insights. Methodology: The main method used statistical analysis, including techniques like Pareto analysis, fishbone diagrams, and Failure Mode and Effects Analysis (FMEA), to identify and solve the root causes of inefficiency. KPIs such as customer satisfaction, occupancy rates, and average daily rates were utilized to assess performance enhancements. Findings: Results show that implementing Lean Six Sigma led to improved operational efficiency, decreased error rates, and better guest experiences. Nonetheless, issues like employee resistance and distribution of resources were observed, highlighting the significance of efficient training and resource management. The research emphasizes the importance of aligning KPIs with strategic objectives and incorporating proactive risk management approaches. Unique Contribution to Theory, Practice and Policy: The implications of these findings extend to improving quality management in hospitality, recommending continuous monitoring, and emphasizing staff engagement for sustained improvements. This research offers actionable insights into the application of quality management systems in the competitive hospitality industry.